Implementing methadone maintenance treatment in prisons in Malaysia - Wickersham, J.A.; Marcus, R.; Kamarulzaman, A.; Zahari, M.M.; Altice, F.L. (2013)
Problem In Malaysia, human immunodeficiency virus (HIV) infection is highly concentrated among people who inject opioids. For this reason, the country undertook a three-phase roll-out of a methadone maintenance treatment (MMT) programme. In Phase 3, described in this paper, MMT was implemented within prisons and retention in care was assessed. Approach After developing standard operating procedures and agreement between its Prisons Department and Ministry of Health, Malaysia established pilot MMT programmes in two prisons in the states of Kelantan (2008) and Selangor (2009) those with the highest proportions of HIV-infected prisoners. Community-based MMT programmes were also established in Malaysia to integrate treatment activities after prisoners' release. Local setting Having failed to reduce the incidence of HIV infection, in 2005 Malaysia embarked on a harm reduction strategy. Relevant changes Standard operating procedures were modified to: (i) escalate the dose of methadone more slowly; (ii) provide ongoing education and training for medical and correctional staff and inmates; (iii) increase the duration of methadone treatment before releasing prisoners; (iv) reinforce linkages with community MMT programmes after prisoners'release; (v) screen for and treat tuberculosis; (vi) escalate the dose of methadone during treatment for HIV infection and tuberculosis; and (vii) optimize the daily oral dose of methadone (>80 mg) before releasing prisoners. Lessons learnt Prison-based MMT programmes can be effectively implemented but require adequate dosing and measures are needed to improve communication between prison and police authorities, prevent police harassment of MMT clients after their release, and improve systems for tracking release dates.